2023
DOI: 10.1097/mlr.0000000000001891
|View full text |Cite
|
Sign up to set email alerts
|

Costs to Implement a Pediatric Weight Management Program Across 3 Distinct Contexts

Natalie Riva Smith,
Meg Simione,
Haley Farrar-Muir
et al.

Abstract: Background: The Connect for Health program is an evidence-based program that aligns with national recommendations for pediatric weight management and includes clinical decision support, educational handouts, and community resources. As implementation costs are a major driver of program adoption and maintenance decisions, we assessed the costs to implement the Connect for Health program across 3 health systems that primarily serve low-income communities with a high prevalence of childhood obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…MGH and Prisma Health had physicians interact with the tools, and their uptake is consistent with the literature regarding the adoption of clinical decision-support tools . Denver Health’s high uptake supported the importance of a team-based care approach, stakeholder engagement, and providing clinician and staff training, which they did extensive engagement and training …”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…MGH and Prisma Health had physicians interact with the tools, and their uptake is consistent with the literature regarding the adoption of clinical decision-support tools . Denver Health’s high uptake supported the importance of a team-based care approach, stakeholder engagement, and providing clinician and staff training, which they did extensive engagement and training …”
Section: Discussionsupporting
confidence: 67%
“…41 Denver Health's high uptake supported the importance of a teambased care approach, stakeholder engagement, and providing clinician and staff training, which they did extensive engagement and training. 20 The previous Connect for Health RCT found that the clinical decision support tools, family educational materials, and text messaging program improved child BMI. 11 In this study, we did not find a change in child BMI, which may be explained by the COVID-19 pandemic and its resultant impacts and related policies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite numerous differences among the remaining studies in this collection, several common themes emerged. Generally, costs are highly variable 26,27 and likely not prohibitive within an overall operational budget. 26,28 Initial costs are increased as preparatory and implementation activities occur, but once launched, ongoing costs may be quite low.…”
Section: Results In Context Of Other Studiesmentioning
confidence: 99%